Blended Experiential Learning with e-Portfolios Learning to Enhance Creative Imagination - N. Sitthimongkolchai; C. Viriyavejakul; S. Tuntiwongwanich (Emerging Science Journal, 2022)
Our research developed out of concerns about whether design students currently have enough creative imagination because of COVID-19, changing design studies to online learning. This paper describes an empirical study testing the effect of Blended Experiential Learning with e-Portfolios Learning on the Creative Imagination of design students to compare the differences in the effectiveness of design students' Creative Imagination scores. It was hypothesized that first-year design students learning through blended experiential learning with e-Portfolios would have higher Creative Imagination scores when compared to those in the control group learning by not following the format. The multistage sampling method was used to select the study population, and the sample consisted of 111 participants. The test was run in two steps, including 1) the try-out, conducted with the sample group of 45 participants using the Dependent T-Test to compare the pre-test and post-test Creative Imagination scores, and 2) the trial run, conducted with the sample group of 33 participants (learning by following the format), and the control group of 33 participants (learning by not following the format) to compare the Creative Imagination scores. MANOVA was then used to test whether at least one component of the creative imagination test scores of the experimental group was higher than the control group. The Test of Creative Imagery Abilities (TCIA) assessment was used to collect the data, which was then analysed using the T-test. Doi: 10.28991/ESJ-2022-SIED-03 Full Text: PDF